An Analysis of Constitutional Court Verdict Number 28/PUU-XI/2013 on Law Number 17 of 2012 About Cooperatives - Marsitiningsih, Marsitiningsih; Inayah, Wafa Nihayati; Putra, Ade Muhammad Syamkirana (Jurnal Dinamika Hukum, 2022)
Article 33 paragraph (1) of the 1945 Constitution and its Explanation which refers to the notion of a typical corporate structure because of the definition of cooperatives in Law Number 17 of 2012 concerning Cooperatives, it turns out that the philosophy is not in accordance with the nature of the economic structure as a joint venture and the kinship-based principle contained in Article 33 paragraph (1) of the 1945 Constitution. Similarly, this understanding has apparently been elaborated in other articles in Law Number 17 of 2012 concerning Cooperatives, thus making the rights and obligations of members by making the supervisory authority too extensively and a capital scheme that prioritizes material and financial capital that overrides social capital which is precisely the fundamental characteristic of cooperatives as a distinct entity of economic actors based on the 1945 Constitution. On the other hand, cooperatives are the same and no different from limited liability companies. This has made cooperatives lose their constitutional soul as an entity of typical economic actors for a nation with a mutual cooperation philosophy.Keywords: Cooperatives, Constitutional Court Verdict, Economy